A COMPARISON OF RHETORICAL MOVES IN STUDENTS' UNDERGRADUATE THESIS ABSTRACT - Mochammad Rizki Juanda, - (2020)
Research on rhetorical move in abstracts has received attention in recent years. However, cross-disciplinary research on rhetorical move in abstract still needs to be done to identify the similarities and differences of the realization of rhetorical moves between different disciplines. This study aims to identify the manifestation of rhetorical moves and linguistic features used in the undergraduate thesis abstracts written by Natural Science and Social Science students in Universitas Pendidikan Indonesia. A total of 120 abstracts were taken from six disciplines (20 abstracts each) i.e. Mathematics, Chemistry, Physics, Geography, Sociology, and History. Hyland's (2000) model was used as the guideline for the analysis. The result showed that Natural Science and Social Science employed different strategies in realizing the moves. Introduction, Methodology and Findings were the most manifested move in Natural Science, while Introduction, Purpose, Methodology, and Findings were the most manifested move in Social Science. The finding on linguistic features, however, showed similar results except in Move 3. In conclusion, the nature of the disciplines does affect the manifestation of rhetorical moves in undergraduate thesis abstracts. It is also revealed that the nature of the move affects linguistic manifestation. This study provides an insight concerning the trend of rhetorical move patterns in both Natural Science and Social Science undergraduate theses. In addition, some suggestions have been provided for further research.